An overview of the first 5 years of the ENIGMA obsessive–compulsive disorder working group: The power of worldwide collaboration. Issue 1 (10th March 2020) - van den Heuvel, Odile A.; Boedhoe, Premika S.W.; Bertolin, Sara; Bruin, Willem B.; Francks, Clyde; Ivanov, Iliyan; Jahanshad, Neda; Kong, Xiang‐Zhen; Kwon, Jun Soo; O'Neill, Joseph; Paus, Tomas; Patel, Yash; et al.
Abstract: Neuroimaging has played an important part in advancing our understanding of the neurobiology of obsessive–compulsive disorder (OCD). At the same time, neuroimaging studies of OCD have had notable limitations, including reliance on relatively small samples. International collaborative efforts to increase statistical power by combining samples from across sites have been bolstered by the ENIGMA consortium; this provides specific technical expertise for conducting multi‐site analyses, as well as access to a collaborative community of neuroimaging scientists. In this article, we outline the background to, development of, and initial findings from ENIGMA's OCD working group, which currently consists of 47 samples from 34 institutes in 15 countries on 5 continents, with a total sample of 2, 323 OCD patients and 2, 325 healthy controls. Initial work has focused on studies of cortical thickness and subcortical volumes, structural connectivity, and brain lateralization in children, adolescents and adults with OCD, also including the study on the commonalities and distinctions across different neurodevelopment disorders. Additional work is ongoing, employing machine learning techniques. Findings to date have contributed to the development of neurobiological models of OCD, have provided an important model of global scientific collaboration, and have had a number of clinical implications. Importantly, our work has shed new light on questions about whether structural and functional alterations found in OCD reflect neurodevelopmental changes, effects of the disease process, or medication impacts. We conclude with a summary of ongoing work by ENIGMA‐OCD, and a consideration of future directions for neuroimaging research on OCD within and beyond ENIGMA.